Regional absorption of talinolol mediated by intestinal transporters: insights from PBPK modeling analysis - Ishida, Kazuya; Liang, Xiaomin; Buyukozturk, Fulden; Hao, Jia; Wan, Christine; Lai, Yurong (Frontiers in Pharmacology, 2026)
Intestinal transporters play a pivotal role in oral absorption dynamics to shape the plasma or blood concentration-time curves of drugs, influencing interindividual pharmacokinetic (PK) variability and drug-drug or drug-food interactions. Plasma concentration-time profiles of several drugs, such as talinolol, bedaquiline, irbesartan, and amisulpride, exhibit dose-dependent dual or multiple absorption peaks, yet the mechanism underlying these phenomena remains elusive. It is hypothesized that the regional expression and interplay of intestinal transporters contribute to the observed dual peaks. To elucidate the mechanisms underlying these unique absorption phenomena, the concentration- and pH-dependent transport of talinolol, a substrate of intestinal transporter P-glycoprotein (P-gp) and organic anion transporting polypeptide (OATP) 2B1, was examined using Caco-2 cells, along with the development of a comprehensive physiologically-based pharmacokinetic (PBPK) model that includes a multi-layer gut wall within an advanced dissolution, absorption, and metabolism (M-ADAM) model built in SimBiology® (MathWorks). The basolateral to apical permeability of talinolol in Caco-2 cells decreased as the extracellular pH decreased at the donor side, but the apical to basolateral permeability did not significantly change, indicating that the transport of talinolol by P-gp is pH-dependent. However, when incorporating Caco-2 permeability data and regional differences in P-gp expression, the PBPK model could not reproduce the plasma concentration profiles of talinolol reported in the literature. Increasing the active uptake on the apical membrane of enterocytes improved the curve fit but did not capture the dual peak profiles. Additionally, adjusting regional transporter activity—specifically lowering apical uptake and/or basolateral efflux transport in the lower jejunum and increasing them in the lower ileum—was key to describing the dual absorption peaks of talinolol. These findings indicate that regional differences in intestinal uptake and efflux influence the complex absorption profiles of talinolol and highlight the need for further investigation into additional transporter roles in basolateral transport in the enterocytes.